2015
DOI: 10.1556/achrom.27.2015.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Selective RP-HPLC DAD method for determination of tenofovir fumarate and emtricitabine in bulk powder and in tablets

Abstract: Summary.A simple and selective liquid chromatographic method was developed for the simultaneous determination of tenofovir disoproxil fumarate (TEN) and emtricitabine (EMT) in combined tablets. The method is based on separation of TEN and EMT on a Zorbax SB-C8 column, 5 μm, 4.6 × 250 mm, with a mobile phase consisting of 50 mM disodium hydrogen phosphate-acetonitrile (50:50, v/v). The mobile phase contains 0.1% triethylamine (TEA) and was adjusted to pH 6.0. Quantification of the analytes is achieved with diod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…TNF was quantified from various active ingredients using HPLC, LC–tandem mass spectrometry (LC–MS/MS; Gollu & Gummadi, 2020; Heydarzadeh et al, 2019; Olejarz et al, 2020; Paritala et al, 2021; Patel et al, 2019; Pavani & Susithra, 2022; Thakare et al, 2023; Xiao et al, 2020; Zhao et al, 2019), spectrophotometry (Buridi, 2013; Ghorpade et al, 2010; Karunakaran et al, 2011), spectrofluorimetry (Tiris et al, 2020), and electrochemical technique (Festinger et al, 2022; Xiao et al, 2022). EMC was analyzed by several techniques, including HPLC (Abdelhay et al, 2015; Haq et al, 2022; Runja et al, 2016), capillary electrophoresis (Guichard et al, 2021), and spectrophotometry (Abdelhay et al, 2013; Ashour & Belal, 2017). BIC was quantified from human plasma using LC–MS/MS (Schauer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF was quantified from various active ingredients using HPLC, LC–tandem mass spectrometry (LC–MS/MS; Gollu & Gummadi, 2020; Heydarzadeh et al, 2019; Olejarz et al, 2020; Paritala et al, 2021; Patel et al, 2019; Pavani & Susithra, 2022; Thakare et al, 2023; Xiao et al, 2020; Zhao et al, 2019), spectrophotometry (Buridi, 2013; Ghorpade et al, 2010; Karunakaran et al, 2011), spectrofluorimetry (Tiris et al, 2020), and electrochemical technique (Festinger et al, 2022; Xiao et al, 2022). EMC was analyzed by several techniques, including HPLC (Abdelhay et al, 2015; Haq et al, 2022; Runja et al, 2016), capillary electrophoresis (Guichard et al, 2021), and spectrophotometry (Abdelhay et al, 2013; Ashour & Belal, 2017). BIC was quantified from human plasma using LC–MS/MS (Schauer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…EMC was analyzed by several techniques, including HPLC (Abdelhay et al, 2015;Haq et al, 2022;Runja et al, 2016), capillary electrophoresis (Guichard et al, 2021), and spectrophotometry (Abdelhay et al, 2013;Ashour & Belal, 2017). BIC was quantified from human plasma using LC-MS/MS (Schauer et al, 2022).…”
mentioning
confidence: 99%
“…The literature search revealed that there are number of analytical methods have been reported for single molecule or simultaneous estimation of TDF and FTC by HPLC [5][6][7][8][9][10][11][12] , by UPLC [13][14][15][16] , by mass spectroscopy 17 . Till date no stability indicating HPLC method has been reported for simultaneous estimation of related substances of TDF and FTC by QbD life cycle approach.…”
Section: Introductionmentioning
confidence: 99%